Analisis Kebijakan Pemerintah Terkait Ancaman Pengangguran Pasca Kenaikan Inflasi - Tan Wan I; Hendra Dewantara; Rahmadhanti Rahmadhanti; Figo Winnerko; Kelvin Yovanka (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstract The purpose of this research is to find out how Indonesia's economic development is by overcoming the effects of inflation and unemployment. This research was conducted in Indonesia by using 5 year time series data. The data used in this study are all data on inflation, unemployment and government policies from 2017 to 2022. In collecting data for this study, data were obtained from BPS and online journals. From the results of the analysis, unemployment and high inflation rates have a major impact on the economic growth of Indonesia. Therefore, the government implements several policies and strategies in an effort to overcome unemployment and inflation, namely monetary policy and fiscal policy. The real problem is that there are clear solutions and policies that have been made, but unfortunately these problems are multidimensional which means that it depends on various sides to be resolved. So based on the problems and strategies that have been made, it can be concluded that behind all policies and strategies, it is still HR who carries out these rules. Keyword : Inflation, Unemployment, Government policies, Indonesia